A novel 1470 nm radial fiber diode for fat harvesting and liposuction. Issue 4 (23rd November 2020) - Robb, Christoper W.; Pozner, Jason N.
Abstract: Autologous fat grafting continues to be a challenge in maintaining viability and survival of grafted fat. Laser‐assisted fat harvesting is a novel concept in liposuction. An all‐in‐one platform that optimizes wavelength, fiber design, cannula design, and current concepts in fat collection and preparation is available that may increase viability of harvested adipocytes and simplify the process. Here, the physics and principals of fat collection are reviewed and discussed in context of this device platform.